Ecological mapping and data quality assessment for the needs of ecosystem-based marine spatial management: case study Greek Ionian Sea and the adjacent gulfs - ISSARIS, Y.; KATSANEVAKIS, S.; PANTAZI, M.; VASSILOPOULOU, V.; PANAYOTIDIS, P.; KAVADAS, S.; KOKKALI, A.; SALOMIDI, M.; FRANTZIS, A.; PANOU, A.; DAMALAS, D.; KLAOUDATOS, D.S.; et al. (Mediterranean Marine Science, 2012)
Mapping of ecosystem components (natural and socioeconomic) is a prerequisite for ecosystem-based marine spatial management (EB-MSM). To initiate the process of EB-MSM in the Greek Ionian Sea and the adjacent gulfs, the main relevant ecosystem components were mapped based on existing spatial information and expert judgment. The natural components mapped included habitat types and species targeted for conservation, according to national and European legislation and international agreements. Main human activities/pressures related to fisheries, aquaculture, tourism, and industry were also mapped. In order to assess the quality of data used to map ecosystem components and therefore take into consideration the inherent uncertainty, an assessment of 5 semi-quantitative data indicators based on a pedigree matrix was conducted. Through this qualitative approach we gained information related to the sources, acquisition and verification procedures, statistical properties, and temporal & geographical correlation, along with the collection process quality of the ecosystem components under study. A substantial overlapping between ecological features and human activities was identified, confirming the need for a well-planned approach to marine space management, in order to mitigate conflicts for marine resources and conserve marine ecosystems and their associated goods and services.